Twisted string actuation with position feedback for robotic endoscopy - Schlesiger Davina; Giacoppo Giuliano A.; Schäfer Max B.; Pott Peter P. (Current Directions in Biomedical Engineering, 2021)
A twisted string actuator (TSA) is a small, strong, lightweight, and low-cost gear, transforming rotation into a linear pulling movement. The TSA consists of two or more strings that are twisted along their common longitudinal axis. The helix formed in this process becomes shorter the further the bundle is twisted. A possible application is a tendon-based endoscopic robot. To control the movement of the endoscope, a precise contraction of the tendon is necessary. Since the strings of the TSA show an elastic behaviour, position feedback is needed to determine the exact movement of the TSA. In this paper, a TSA with a closed-loop position control by a low-cost displacement sensor is presented.